The Boogeyman: Derek Boogaard and the Detrimental Effects of Section 301 Preemption - Tyler V. Friederich (Washington University Law Review, 2017)
This Note focuses on the preemptive effect of section 301 of the Labor Management Relations Act (LMRA) in the suit against the National Hockey League (NHL) by the Estate of former NHL player Derek Boogaard. The Note will contrast Boogaard v. National Hockey League, in which section 301 preempted the Estate’s negligence claims, with several National Football League (NFL) cases. Boogaard will also be contrasted with In re National Hockey League Players’ Concussion Injury Litigation, a similar case brought by a class of NHL players in which the court declared that section 301 did not preempt claims for negligence at the motion to dismiss stage.3 The following analysis of section 301 preemption and Boogaard will reveal inequities and flaws inherent in section 301 preemption that should be removed by Congress. It also analyzes avenues future litigants may pursue to circumvent section 301 preemption altogether. First, this Note will discuss Derek Boogaard’s career as an NHL enforcer. Then, it will explain the history of the LMRA and section 301 preemption. A synopsis of relevant NFL cases will follow and provide examples of when section 301 has, and has not, preempted negligence claims brought by former players. Next, the Note will analyze Boogaard and contrast its outcome with the aforementioned NFL cases. An analysis of Concussion Injury will follow that discusses why its outcome differed from Boogaard. Finally, this Note will argue that the preemptive effect of section 301 did not serve its intended purpose in Boogaard and that Congress should place restrictions in its application—such as extending the statute of limitations period—and show how future NHL players can apply lessons learned from Boogaard and Concussion Injury to circumvent section 301 preemption in state-law tort claims.
Keywords: National Hockey League; NHL; Section 301 Preemption; Derek Boogaard; Labor Management Relations Act; LMRA; In re National Hockey League Players’ Concussion Injury Litigation; Boogaard v. National Hockey League